Evaluation of training curriculum in terms of pressure and threshold indexes of for 400m Iraqi national athletics team players - Kahdim, M. J.; Jewdi, Z. J. M.; Shehab, G. M.; Hamedi, M. H. (Journal of Human Sport & Exercise, 2019)
The environment material of this study is the Iraqi athletic team and the research field is to evaluate specific training curriculum by investigating the pressure and anaerobic threshold indexes for 400m sprint activity. Initially, it is assumed that there will be differences of statistical significance in both of the indexes in the primary and final tests. It is more suitable to implement the descriptive method to the 6 samples of this study and to the selection of physiological indexes directly after exercise tension. After collecting and analysing the experimental data statistically, it seems to have an improvement in systolic and diastolic blood pressure by the end of the training program. However, the result shows that there is no genuine change in anaerobic threshold index.